1996
DOI: 10.1021/bi960098n
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular and in Vitro Transport of Glutathione Conjugates by MRP

Abstract: MRP is a recently identified ATP-binding cassette transporter. We previously established that MRP confers resistance to a spectrum of natural product cytotoxic drugs [Kruh, G.D., (1994) Cancer Res. 54, 1649-1652], that expression of MRP is associated with enhanced drug efflux [Breuninger, L.M., (1995) Cancer Res. 55, 5342-5347], and that MRP transcript is widely expressed in human tissues and solid tumor cell lines [Kruh, G.D., (1995) J. Natl. Cancer Inst. 87, 1256-1258]. In the present study the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…Using membrane vesicle transport assays, we demonstrate in this report that MRP also pumps a spectrum of natural product cytotoxic drugs. The specificity of MRP for both classes of compounds is consistent with our observations that daunorubicin transport is inhibited by drug glutathione conjugates and that APA-SG transport is inhibited by natural product drugs (29). Analysis of the kinetics of inhibition further suggests that these diverse substrates may share a common binding site on the transporter.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Using membrane vesicle transport assays, we demonstrate in this report that MRP also pumps a spectrum of natural product cytotoxic drugs. The specificity of MRP for both classes of compounds is consistent with our observations that daunorubicin transport is inhibited by drug glutathione conjugates and that APA-SG transport is inhibited by natural product drugs (29). Analysis of the kinetics of inhibition further suggests that these diverse substrates may share a common binding site on the transporter.…”
Section: Resultssupporting
confidence: 87%
“…This possibility was examined by determining the effect of drug glutathione conjugates on daunorubicin transport. We have observed in vitro transport of the glutathione analog APA-SG by MRP (29) and transport of the drug glutathione conjugate DNP-SG has also been reported (15,16). Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Mutations of lysine residues in the Walker A motif of the first and second nucleotide binding domains of MRP decreased drug resistance levels compared with wild-type MRP (5), implying that MRP functions as an ATP-dependent drug pump. Its function has been studied widely using membrane vesicles prepared from MRP-expressing cells (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). It was found that anticancer drugs, such as vincristine, cannot be transported by MRP, unless glutathione is also present (13).…”
mentioning
confidence: 99%
“…However, there is no direct evidence that MRP can bind unmodified forms of the drugs to which it confers resistance, and there are conflicting reports of its ability to transport these compounds (17)(18)(19). MRP can function as a primary active ATP-dependent transporter of cysteinyl leukotrienes, other organic glutathione conjugates including oxidized glutathione, as well as etoposide glucuronide, certain steroid glucuronides, and bile salt derivatives (18 -24).…”
mentioning
confidence: 99%